Transforming an Edwardian boarding house into an urban marae at Auckland University College in 1954 - Tyler, Linda (Architectural History Aotearoa, 2015)
In writing the history of art in Aotearoa/New Zealand, much attention has been focussed on the exhibitions and activities of painters and sculptors of the Māori Renaissance in the 1950s. Equally significant was the impetus given to reviving customary crafts through the Adult Education movement associated with the University of Auckland. The Maori Social and Economic Advancement Act of 1945 positioned the responsibility for preservation, revival and maintenance of "Māori arts, crafts, language, genealogy and history" with iwi, and led to the formation of the Maori Women’s Welfare League in September 1951, with its agenda to perpetuate women’s skills in Māori arts and crafts, and for these to be practised within an architectural context. A Māori advisory committee was established in the Adult Education Centre at Auckland University College in 1945, tasked with mitigating Māori urban alienation through the teaching of Māori arts and cultural history to establish "pride of race and cultural achievement." In 1949, the first tutor for the Maori Adult Education Extension Programme was appointed, Maharaia Winiata (1912-60), followed by a graduate of the Rotorua School of Māori Arts and Crafts, Master carver Henare Toka (Ngāti Whatua) and his wife Mere. They recruited students from the Auckland University College Māori Club and pupils from Māori secondary schools to decorate the entrance hall of Sonoma House, 21 Princes Street, with kōwhaiwhai and tukutuku. Thus an Edwardian building was reborn as the University’s Adult Education Centre, and was acclaimed for its biculturalism in the spring issue of Te Ao Hou in 1954. Now 60 years old, the tukutuku panels have been preserved by present day Deputy Vice Chancellor Jim Peters in the ground floor of the University’s Clocktower following the disestablishment of Adult Education. Seven of these tukutuku panels have recently undergone extensive conservation treatment, and they are recognised as highly significant examples of twentieth century weaving, exemplifying the approach to reviving customary tukutuku at mid-century in terms of the materials and techniques as well as patterns: muumuu, or purapura whetuu roimata toroa), waharua koopito, whakarua koopito, niho taniwha and nihoniho. They have now gone on display in pride of place in the University Clocktower. This paper will contextualise the changing meaning of these tukutuku panels from interior décor to historic design within the evolving narrative of customary Māori weaving practices.